НЕСОВЕРШЕННЫЙ ОСТЕОГЕНЕЗ: ПОЛИМОРФИЗМ КЛИНИЧЕСКИХ ПРОЯВЛЕНИЙ И ТАКТИКА ЛЕЧЕНИЯ - И. А. Викторова; Н. В. Коншу; Д. С. Иванова (Архивъ внутренней медицины, 2015)
Osteogenesis imperfecta syndrome characterized by clinical manifestations of polymorphism under light for a long time can not be diagnosed, and it becomes apparent only after the symptoms found in children and grandchildren these patients. Management of patients with this nosology requires a multi-component approach in the context of the family with questions of prevention of recurrent fractures, treatment, rehabilitation and disability.